Precession- and Obliquity-Induced Changes in Moisture Sources for Enhanced Precipitation Over the Mediterranean Sea - Bosmans, J. H.C. (author); van der Ent, R.J. (author); Haarsma, R. J. (author); Drijfhout, S. S. (author); Hilgen, F. J. (author) (Paleoceanography and Paleoclimatology, 2020)
Enhanced winter precipitation over the Mediterranean Sea at times of minimum precession and maximum obliquity, that is, times of enhanced insolation seasonality, could provide freshwater required to form orbitally paced sedimentary cycles across the Mediterranean, offering a possible alternative to monsoonal runoff. We investigate the sources of the enhanced winter precipitation, by applying a moisture tracking model on the results of idealized orbital extreme experiments with a state-of-the-art climate model. Precession and obliquity enhance precipitation in fall and winter. Our study shows that the source of enhanced precipitation over the Mediterranean Sea differs during the winter half-year. In fall, the majority of the precession-induced precipitation increase originates from the Mediterranean itself. However, in late winter, the increase can be attributed to enhanced moisture advection from the Atlantic. This agrees with changes in evaporation and air-sea temperature differences over the Mediterranean. The obliquity-induced precipitation increase shows much less differences, with an equal contribution of local and Atlantic sources. The mechanism behind the Atlantic source of moisture, particularly important in late winter for precession-induced precipitation changes, is related to a weakened Azores High and slightly higher surface pressure over North Africa. The resulting anomalous circulation patterns generate enhanced Atlantic moisture transport toward the Mediterranean. These mechanisms coincide with weaker storm track activity over the North Atlantic, opposite to previous studies that often attribute enhanced Mediterranean winter precipitation to a southward shift and intensification of the Atlantic storm track. We thus provide an alternative mechanism for Atlantic sources of orbitally paced Mediterranean precipitation changes. Water Resources